2016
DOI: 10.5433/1679-0359.2016v37n6p3859
|View full text |Cite
|
Sign up to set email alerts
|

Physiological quality of the seeds of common bean cultivars grown in different phosphorus levels and growing seasons

Abstract: The use of appropriate management practices, such as sowing and fertilizing, associated with the use of promising genotypes are strategies for obtaining bean seeds of high quality. The aim of this study was to evaluate the physiological quality of cultivars of common bean seeds produced in two growing seasons under different phosphorus levels. The experimental design was completely randomized in a factorial design of 2 × 2 × 6, with four replications. We evaluated two common bean cultivars ('IAC Carioca Precoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…The common bean (Phaseolus vulgaris L.) is one of the most important legumes for the human diet, due to its high nutritional quality (20-25% protein), vitamins, and minerals (Broughton et al, 2003). Brazil is considered one of the largest producers worldwide of this legume (Zucareli et al 2016). Low inputs requirement, high economic value, and adequate climate conditions enabling production over three growing seasons throughout the year (Aug.-Nov., Dec.-Mar., and Apr.-Jul.).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The common bean (Phaseolus vulgaris L.) is one of the most important legumes for the human diet, due to its high nutritional quality (20-25% protein), vitamins, and minerals (Broughton et al, 2003). Brazil is considered one of the largest producers worldwide of this legume (Zucareli et al 2016). Low inputs requirement, high economic value, and adequate climate conditions enabling production over three growing seasons throughout the year (Aug.-Nov., Dec.-Mar., and Apr.-Jul.).…”
Section: Introductionmentioning
confidence: 99%
“…A feasible alternative to reduce the yield gap in these areas is the adoption of high quality seeds, which have resulted in good agronomic performance and consequently high yields. High quality seeds possess great genetic, physical, physiological, and sanitary attributes (Zucareli et al, 2016), which helps crops withstand environmental stresses and defend against pests and diseases. Among those attributes, physiological quality is one of the most important and is related to the ability that seeds have in performing vital functions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of seeds with high physiological potential is related to their ability to perform vital functions, characterized by longevity, germination, and vigor (Cardoso et al, 2012). However, these characteristics may be influenced by the genotype (Mambrin et al, 2015), environmental conditions of its production and season yields (Zucareli et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…However, in regions with a warmer climate, such as the North of Minas Gerais, for cultivation in drought and winter seasons, there is a greater advantage in cultivation in the harvest of the waters due to the higher temperatures that tend to cause greater abortion of flowers (Didonet & Vitoria, 2006), greater competition with weeds (Barrosos et al, 2010), and the risk of harvesting in the rainy season (Araújo & Camelo, 2015), impairing the production of good quality seeds. Zucareli et al (2016) reported that bean cultivation in the dry season provides seeds with greater germination and vigor compared to the harvest of the waters.…”
Section: Introductionmentioning
confidence: 99%